Removal of Siloxanes from Biogas - Hepburn, Caroline Amy (Cranfield University, 2014)
Economic utilisation of biogas arising from sewage sludge is hampered by the need to remove siloxanes, which damage gas engines upon combustion. This thesis applies on-line Fourier transform infrared spectroscopy to measure siloxanes in biogas upstream and downstream of the activated carbon vessels designed to adsorb siloxanes. On-line analysis provides accurate measurement of siloxane concentrations with a detection limit below the siloxane limits set by engine manufacturers, high data intensity and timely identification of breakthrough. Cost savings of up to £0.007 kWh- 1 may be realised compared to existing grab sampling. Using on-line analysis, the performance of full-scale and bench-scale carbon vessels were measured. Full-scale carbon contactors are typically operated at Reynold’s numbers close to the boundary between the laminar and transitional regimes (Re = 40 - 55). This thesis demonstrates, at full- and bench-scale, that increasing the Reynold’s number to site the adsorption process in the transitional regime increases media capacity, by 36% in dry gas and by 400% at 80% humidity. It is postulated that the change in gas velocity profile which occurs as Reynold’s number increases reduces the resistance to siloxane transport caused by gas and water films around the carbon particles, and therefore increases the rate of the overall adsorption process. In the laminar regime (Re = 31) increasing humidity from zero to 80% led to the classical stepwise reduction in adsorption capacity observed by other researchers, caused by the increasing thickness of the water film, but in the transitional regime (Re = 73) increasing humidity had no effect as no significant water film develops. It is therefore recommended that siloxane adsorption vessels should be designed to operate at Reynold’s numbers above 55. By choosing a high aspect ratio (tall and thin) both Reynold’s number and contact time can be optimised.
Keywords: Activated carbon; Adsorption; Anaerobic digestion; FTIR spectroscopy; Hydrodynamic regime